Penyuluhan Hukum Berkas Digital Pembebasan Tanah Adat di Kabupaten Sarmi - Andrian Sah; Suwito Suwito; Revie Kurnia Katjong; Jusmawati Jusmawati; Irsan Irsan; Wahyudi BR; Asmarani Ramli (Jurnal Pengabdian Literasi Digital Indonesia, 2023)
In 1997 the government has regulated the policy of Granting Ownership Rights for Very Simple Houses and Simple Houses through KMNA/KBPN No. 9 of 1997 and KMNA/KBPN No. 6 of 1998 concerning the Granting of Property Rights for Residential Houses. The existence of this decision is very beneficial for landowners and residential houses in housing complexes built by developers and for Indonesian citizens who own land with Building Use Rights for residential homes to have the convenience of obtaining changes in land rights to ownership rights. To address that in laws and regulations, regulations regarding changes in the status of Building Use Rights to Property Rights, it is deemed necessary to provide counseling/lectures so that the community in Dok IX Jayapura Utara Province of Papua knows the process and obstacles encountered in changing the status of Building Use Rights become property. Counseling/lectures on the topic of changing the status of Building Use Rights to Property Rights involved lecturers at the Faculty of Law at Yapis University in Papua as a service team and involved Lecturers at the Faculty of Law at Yapis University in Papua. The community service activities carried out at IX Jayapura Utara, Papua Province, can be said to have been carried out well as expected.act.